Syntheses and structure-activity relationship studies of schwarzinicine alkaloids as vasorelaxant agents - Lee, Fong Kai (2020)
Hypertension has emerged as one of the leading risk factors responsible for global burden and mortality. Among the hypertensive patients, there is a segment of patients who are suffering from resistant hypertension, whose blood pressure cannot be controlled despite concurrently taking three or more classes of antihypertensive drugs. The adverse effects associated with the common classes of antihypertensive agents used have limited the combinations available to be used in treating resistant hypertension. Natural products play a vital role in drug discovery and development as they represent promising sources of useful lead molecules, in which they might be able to address the resistant hypertension issue. Our group has recently isolated from a previously uninvestigated Ficus species (F. schwarzii) a series of nine new phenethylamine alkaloids, namely, schwarzinicines A–G (142–148) and schwarzificusines A (149) and B (150). Schwarzinicine A (142), being the most abundant alkaloid of this series, was found to exhibit pronounced vasorelaxant effects in rat isolated aorta. In this study, we have successfully developed the total syntheses of schwarzinicines A (142), B (143) and F (147). In order to explore the active pharmacophore of schwarzinicine A (142) as a lead compound for vasorelaxation, several series of analogues were designed, synthesized and evaluated for their vasorelaxant activity for structure-activity relationship (SAR) analysis. In addition to the discovery of 13 synthetic analogues that were shown to be promising for further development, the SAR study revealed a few structural features that are associated with enhancement of vasorelaxant effects. These structural features could be useful to design better vasorelaxant agents in the future.